A Reversible Liquid‐to‐Liquid Organic Hydrogen Carrier System Based on Ethylene Glycol and Ethanol. Issue 67 (29th September 2020) - Zhou, Quan‐Quan; Zou, You‐Quan; Ben‐David, Yehoshoa; Milstein, David
Abstract: Liquid organic hydrogen carriers (LOHCs) are powerful systems for the efficient unloading and loading molecular hydrogen. Herein, a liquid‐to‐liquid organic hydrogen carrier system based on reversible dehydrogenative coupling of ethylene glycol (EG) with ethanol catalysed by ruthenium pincer complexes is reported. Noticeable advantages of the current LOHC system is that both reactants (hydrogen‐rich components) and the produced esters (hydrogen‐lean components) are liquids at room temperature, and the dehydrogenation process can be performed under solvent and base‐free conditions. Moreover, the hydrogenation reaction proceeds under low hydrogen pressure (5 bar), and the LOHC system has a relatively high theoretical gravimetric hydrogen storage capacity (HSC>5.0 wt %), presenting an attractive hydrogen storage system. Abstract : Hydrogen carriers : A liquid‐to‐liquid organic hydrogen carrier system based on reversible dehydrogenation and hydrogenation reactions by using ethylene glycol and ethanol is reported. Both the reactants are abundant, cheap, and non‐toxic industrial raw materials. Moreover, this dehydrogenative esterification, as well as hydrogenation, can be conducted under base‐ and solvent‐free conditions, thus offering a promising approach for application in hydrogen storage.